Pemanfaatan Teknologi Digital Untuk Meningkatkan Kemampuan Literasi dan Numerasi Anak Usia Dini - Sri Sufliati Romba; Nursalam; Andi Tenri Ampa (Ikatan Ahli Informatika Indonesia, 2024)
This study aims to determine the effectiveness of using digital technology media to improve early childhood numeracy literacy skills in the learning process. If children have good literacy and numeracy skills at an early age, they are building the foundation of knowledge and skills that they need to learn at a higher level. Therefore, effective and innovative learning approaches are needed, such as the use of digital technology media which is utilised to improve children's literacy skills in a fun and interactive way from an early age. This type of research uses a descriptive quantitative approach, with a population of 30 children. Data collection techniques were carried out using observation and documentation methods and using data processing normality test, homogeneity test, and one-sample test. In the One sample test, the Significance Two-Sided p value is 0.01, <0.05 and the Mean difference of the initial observation is 48.500 and the second observation is 70.167, it is found that there is a difference in the average increase from the initial observation and the second observation. Based on the results of the calculation, it is concluded that the use of Digital Technology media in learning greatly helps the development of Early Childhood Literacy and Numeracy, namely in terms of creativity, reading skills, counting skills, and writing skills, and encourages interest/reading habits at Bukit Permai Agang Je’ne Kindergarten.